The Influence of Digital Parenting on the Social Behavior of Early Childhood in the 5.0 Technology Era - Sari, Mega Mustika; Syawaludin, Dwi Febri (Jurnal Multidisiplin Indonesia, 2024)
The rapid advancement of technology in the 5.0 era has significantly influenced various aspects of life, including early childhood development. One of the most notable changes is the role of digital parenting, where parents utilize digital tools and platforms to guide and manage their children's upbringing. As children increasingly engage with digital content, understanding the effects of digital parenting on their social behavior becomes critical. This study aims to explore the influence of digital parenting on the social behavior of early childhood in the 5.0 technology era, examining both positive and negative impacts of technology exposure on social interactions and communication skills. A qualitative research design was employed, utilizing surveys and in-depth interviews with parents, teachers, and child development experts. Data were collected from parents with children aged 3 to 6 years who are actively engaged with digital devices at home. The study finds that digital parenting has a mixed effect on children's social behavior. On the positive side, it facilitates learning and enhances communication skills, while on the negative side, excessive screen time can lead to social isolation, reduced face-to-face interaction, and impaired social skills. Parents who balance screen time with offline social activities tend to foster better social behavior in their children.